RECONSTRUCTIVE OPERATIONS ON THE PERMANENT VASCULAR ACCESS FOR HEMODIALYSIS - V. I. Lotts; L. E. Osipov; V. N. Sergeev (Вестник трансплантологии и искусственных органов)
In patients with end stage renal failure it is vitally necessary to have permanent long functioning vascular access, providing all requirements of modern hemodialysis. Authors have evaluated the terms of functioning of arterio- venous fistulas after operations at 56 patients. Undertaking reconstructive operation on arteriovenous fistula allows to enlarge duration of the permanent vascular access function for two years in average.